Education of interned soldiers of Ukrainian People’s Army in Poland: the case of the camp in Aleksandrów Kujawski - Zbigniew Karpus; Olena Humeniuk (Cхід, 2019)
The purpose of the article is to analyze the educational activity – the system of its organization and directions peculiar to the military servants of the Army of the Ukrainian People’s Republic (UNR) interned in camps of Poland in the early 1920s. On the example of the organization of education in the camp in Aleksandrów Kujawski, a comparative analysis was made for other camps in Poland, where members of the UNR Army were stationed. The methodology of the research is based on the application of general historical methods of scientific research, namely: historical-comparative, typologization (historical-typological) and systematic analysis. An analysis of the peculiarities of the organization, methodological framework of the educational work of the interned military servants as part of the general cultural and educational activity of the Ukrainian interwar emigration is conducted for the first time, their effectiveness for obtaining higher education or the possibility of further professional activity outside the camp is also determined.